A spiral design: redesigning CS 1 based on techniques for memory recall - Lionelle, Albert, author; Beveridge, J. Ross, advisor; Ghosh, Sudipto, committee member; Blanchard, Nathaniel, committee member; Folkestad, James, committee member (Colorado State University. Libraries, 2021)
Computer Science (CS 1) offerings in most universities tend to be notoriously difficult. Over the past 60 years about a third of students either fail or drop out of the course. Past research has focused on improving teaching methods through small changes without changing the overall course structure. The premise of this research is that restructuring the CS 1 course using a Spiral pedagogy based on principles for improving memory and recall can help students learn the information and retain it for future courses. Using the principles of Spacing, Interleaving, Elaboration, Practiced Retrieval, and Reflection, CS 1 was fundamentally redesigned with a complete reordering of topics. The new pedagogy was evaluated by comparing the students with those coming from a traditional offering in terms of (1) CS 1 performance, (2) CS 2 performance, and (3) retention of students between CS 1 and 2. Additionally, students were tracked on the individual outcome / topic level of their performance, and students filled out surveys measuring learning motivation and self-regulation. The Spiral pedagogy helped students outperform those who learned via the traditional pedagogy by 9% on final exam scores in CS 1 with a significant difference. Furthermore, 23% of students taught using the Spiral pedagogy mastered greater than 90% of the outcomes, where those taught with the traditional method only mastered 5% of the learning outcomes. Students who were taught with the Spiral pedagogy showed a greatly increased interest in Computer Science by the end of the course, with women showing the greatest increase in interest towards Computer Science. Retention is increased between CS 1 and CS 2 with a 19.2% increase for women, and a 9.2% increase overall. Five weeks later, students were given the same final exam by way of a review exam in CS 2. With the gap in time to forget, those taught with the Spiral pedagogy scored 10-12.5% higher than their peers taught using the traditional method. The change in pedagogy showed an influence with Cohen's d = .69. Furthermore, students continued to do better in CS 2 with increased grades across all assessments, including programming capabilities. By the end of CS 2 only 65% of students who learned by the traditional method passed CS 2 with a C or above while students who learned via the Spiral pedagogy had 80% pass with a C or above. The framework for the Spiral Design is presented along with implementation suggestions if others wish to duplicate the pedagogy for their course along with future research suggestions; including building a Spiral Curriculum to enhance performance across courses and interactive tools to act as a means of intervention using techniques proven to improve recall of past content. Overall the Spiral Design shows promising results as the next generation in course design for supporting student achievement and provides additional pathways for future research.
Keywords: Computer Science Education; Performance; Spiral Design; Outcome Tracking; Computer Science 1; Recall